Validation of +tiDx: a point-of-care diagnostic system for Gram-positive bovine mastitis - Restrepo-Cano, Valentina; Caraballo-Guzmán, Arley; Sánchez-Jiménez, Miryan Margot; Torres-Lindarte, Giovanny (Frontiers in Veterinary Science, 2026)
IntroductionRapid and accurate detection and identification of bovine mastitis-causing pathogens are crucial for treatment decisions and dairy farm management. In this work, we developed and validated a diagnostic system for point-of-care applications that may properly detect and identify Staphylococcus aureus, Streptococcus agalactiae, non-aureus staphylococci, and other Streptococcus species, which are all considered as relevant pathogenic species for bovine mastitis in Colombia. The diagnostic system is supported by a mobile application, +tiApp, that facilitates result interpretation, digital record keeping, and provides evidence-based treatment recommendations to assist on-farm decisions.MethodologyA total of 520 milk samples from cows with somatic cell count (SCC) < 200,000 cells/ml, or < 100,000 cells/ml for primiparous cows, which were deemed free of intramammary infection, and subclinical mastitis cows (>200,000 cells/ml, or >100,000 cells/ml for primiparous cows) were analyzed using the +tiDx system and a composite reference standard (CRS), which included standard microbiological culture (SMC) and SCC as testing conditions, to assess diagnostic performance for detection and identification of Gram-positive pathogens. We evaluated our diagnostic system by REASSURED criteria against the SMC.ResultsThe +tiDx diagnostic system demonstrated adequate overall performance relative to CRS for the detection of mastitis caused by Gram-positive bacteria, achieving a sensitivity of 0.98 and a specificity of 0.94 relative to CRS. Regarding its performance relative to CRS against specific pathogens, the system yielded varied yet noteworthy results depending on the evaluated species: a sensitivity of 0.65 and specificity of 0.94 for S. aureus; 0.82 sensitivity and 0.93 specificity for S. agalactiae; 0.36 sensitivity and 0.98 specificity for non-aureus staphylococci; and values of 0.98 sensitivity and 0.92 specificity for other Streptococcus species. Cohen's kappa coefficient was 0.92, indicating high concordance between the in-laboratory diagnostic system and CRS, while concordance between the on-field diagnostic system and CRS was 0.74.Conclusion+tiDx is a practical and reliable on-farm diagnostic tool for Gram-positive intramammary infections, combining timeliness and ease of use with appropriate user training to ensure accurate result interpretation and support effective mastitis control.